Leaf stomatal traits variation within and among black poplar native populations in Serbia - Čortan, Dijana; Vilotić, Dragica; Šijačić-Nikolić, Mirjana; Miljković, Danijela (BOSQUE, 2017)
Populus nigra as a keystone riparian pioneer tree species is one of the rarest and most endangered species in Europe due to the loss of its natural habitats. Genetic diversity existence is a key factor in survival of one species, and stomata as genetically controlled trait could be used for differentiation studies. With the aim of proving stomatal phenotypic variation of the four native populations of Populus nigra located on the banks of three biggest river valleys (Dunabe, Tisa and Sava) in the region of Vojvodina in northern Serbia, we examined various leaf stomatal traits (stomatal length and width, pore length and width, stomatal density, shape coefficient and stomatal and pore area). We tested the differences of stomatal traits among populations, interindividual variability - differences among trees, the intraindividual variability, the differences between sun-exposed and shaded leaves, among leaves nested in exposition and the differences in adaxial and abaxial leaf surface. Based on mixed model ANOVA results, interpopulation variability, as statistically significant differences, observed only for stomatal pore length and shape, while all examined traits showed interindividual variability. On the intraindividual level the results showed differences for stomatal traits, except for stomatal width, stomatal shape coefficient and stomatal density regarding leaf exposure. For better understanding of how morphological and stomatal characteristics vary in black poplar populations, further studies should be necessary involving controlled environmental conditions with the aim of examining phenotypic plasticity to changing climate conditions.